PENERAPAN METODE ASYNCHRONUS DALAM PEMBELAJARAN MAHARAH KITABAH DI PJJ PAI IAIN SYEKH NURJATI CIREBON - Mohammad Shohibul Anwar; Rodiatul Maghfiroh; Nurhadi Nurhadi; Wildana Wargadinata (AL-MUARRIB: JOURNAL OF ARABIC EDUCATION, 2023)
The industrial revolution 4.0 has changed the paradigm of education and encouraged the use of Distance Learning (PJJ) as an alternative in the learning process by utilizing technology. However, this transition also causes students to be less adaptive and passive in learning Arabic, especially in writing skills (maharah kitabah) at PJJ IAIN Syekh Nurjati Cirebon. Therefore, this study aims to explore the Asynchronus method by applying online discussions as a strategy in learning maharah kitabah. This research uses qualitative research methods with a case study approach. The research sample consisted of 44 students who participated in maharah kitabah learning during PJJ. Data was collected through observation and interviews. In addition, the Likert scale is used to measure students' perceptions of the application of online discussions in learning maharah kitabah. The results showed that the Asynchronus method with the application of online discussions significantly improved students' ability to express thoughts in writing in Arabic. Online discussions provide an opportunity for students to interact with fellow students and discuss maharah kitabah topics. In addition, students reported that through online discussions, they felt more confident in expressing thoughts and ideas in Arabic writing. Being actively involved in discussions, receiving positive feedback, and seeing improvements in their writing skills makes students feel more confident in using Arabic effectively.